FORMATION OF STUDENTS ’SKILLS AND SKILLS OF INTELLECTUAL INTERACTION - Amelina С. М. (Pedagogy of Higher and Secondary Education, 2011)
The article considers the problem, ways and means of effective formingof the intellectual interaction skills.